Communicative versus linguistic competence: the case of primary school students with Portuguese as an Additional Language - Rosa, A. (Advanced Research Seminar on 4 February 2021 organised by CETAPS / TEALS, FCSH, Universidade Nova de Lisboa, 2021)
It is common that students with a native language different than the one used in the formal curriculum are treated as cases requiring a “special” treatment, often translated in extra-curricular hours of linguistic assistance, or even in their exclusion from activities requiring a good use of the formally taught language. This phenomenon is especially evident in Portugal due to the strong migration movements since the late ´60s. Especially in primary school, the lack of programmes specialised in children with Portuguese as an Additional Language (PLA) has called for our attention. The object of this study is the communicative competence of children with PLA, inserted in the Portuguese primary school environment, with the goal of showing how a language that is not perfectly spoken, from a grammatical and syntactic point of view, is not a barrier in these children’s interaction both with their Portuguese peers and their teachers. Adopting the ethnomethodological paradigm, the observation of ten children with PLA was performed during their performance of communicative activities in the classroom and during playtime. The conversational analysis of a large corpus of interactions collected during two years from two different schools allowed the identification of some of the devices mobilized in the conversations of the children with PLA. Some of the communication devices identified were: (a) the categorization devices used by students in the construction of institutional identities of the school members; (b) the conversational organization of turns’ alteration in interactions both with peers and the teachers; (c) the effective coordination of intelligible actions, such as textual understanding or the use of laughter as a communicative device. It is concluded that based on the observed communicative phenomena, children with PLA can participate effectively in formal and informal contexts of interaction. In addition, it is argued how, from an ethnomethodological perspective, it could be possible to promote some reflections on the organization of talk-in-interaction within the plurilingual environment of the Portuguese public school.